Comparative Characteristics of Various Cereals in Terms of Fodder Value, Antinutrients and Use for Poultry Feeding - Olena V. Gaviley; Oleg O. Katerynych; Igor A. Ionov; Darren K. Griffin; Olena O. Dekhtiarova; Michael N. Romanov (Encyclopedia, 2025)
The primary ingredients in poultry feed, cereals, are among the most widely used crops in worldwide agriculture, with principal staples being wheat, rice, corn (maize), sorghum, barley, oat and millet. The scope of this review is to provide a detailed comparative analysis of the nutritive values of cereal crops, and the antinutrients they contain, with reference specifically to their use for feeding poultry. These cereal crops range in biological value from 55 to 77.7%, in protein digestibility from 77 to 99.7%, and in net protein utilization from 50 to 73.8%. Most essential amino acids, including lysine, are found in cereal grains, whereas the nutritional value of cereals is impacted by antinutritional elements. These include non-starch polysaccharides (NSPs), such as pentosans (arabinoxylans) and β-glucan, as well as alkylresorcinols. Around 100 g/kg of pentosans are found in rye, 50–80 g/kg in wheat and 68–92 g/kg in triticale. There are strategies to reduce NSPs and other antinutrients and maximize the effectiveness of utilizing grains in compound feed for poultry. These include the application of enzyme preparations, along with dry and wet extrusion methods, for processing grains. By restricting our narrative to a direct comparison of all major staples for poultry feed, we conclude that further research is required specifically in the area of determining how economically viable it is to feed adult and young chickens with compound feeds containing various cereal crops. Furthermore, we speculate on the utility of employing enzyme preparations and extrudates to maximize feed efficiency.